The risks and perceived rewards of rising revivalist populism in Malaysia - Mohamad Shukri, Syaza Farhana (ISEAS - Yusof Ishak Institute, 2024)
Recently, Malaysia has experienced a palpable surge in populism that has swept across the nation’s political and social landscape, stirring debate and discord. The case of Akmal Saleh, leader of UMNO’s youth wing, and the unfortunate saga concerning socks adorned with the word “Allah” serve as a poignant reflection of this trend. This incident is symptomatic of a larger, more concerning pattern of revivalist populist politics in Malaysia. This type of populism often emerges in response to perceived threats to national identity, culture, or the socioeconomic status quo, positing a return to ‘the good old days’ of Malay political hegemony.